Increasing the Duration of Eye Contact in Children with Autism Through the Look and Say Technique - Semi Tarappak Panggoa; Dwiyatmi Sulasminah; A. Mappincara; Tatiana Meidina (Jurnal Penelitian Pendidikan IPA, 2023)
The main problem taken to conduct this research is children with autism who experience low ability to make eye contact. This study aims to determine whether extended eye contact can be achieved by autistic individuals using the look technique. The purpose of this study is to learn how to improve the capacity of grade 4 autistic students to make eye contact. This study employs experimental research methods and a Subject Research Strategy (SSR) using an A-B-A design. The collected data will then be subjected to quantitative statistical processing before being displayed as percentages, graphs, and means. According to the study's findings, kids have a poor capacity to create eye contact before using the Look technique. (1) There was relatively little eye contact with the NA participant prior to using the Look method. (2) The NA participant had eye contact for a longer period of time after receiving the gaze method, reaching the high category. (3) For autistic children who have received treatment utilizing the Look approach, the amount of eye contact is sufficient. (4) While the value attained by NA individuals was higher than before receiving treatment, the capacity of NA subjects to extend contact time in baseline 1 (A1) settings in baseline 2 (A2) after receiving therapy declined from a high category to an adequate category in intervention condition B. This demonstrates how the Gaze method encourages extended eye contact in autistic kids. This is a result of the intervention's effect